Identification of Borassus Flabellifer Sap Compounds Against Angiotensin- Converting Enzyme for Potential Antihypertensive Inhibitors: Life Sciences-Medicine - Shobana, M; Thilagavathi, S (International Journal of Life Science and Pharma Research, 2022)
On a global scale, cardiovascular problems have become more important recently. The existing treatments for high blood pressure are generally unsuccessful and painful for patients. Since it poses a significant risk to the cardiovascular system and the general public's health, hypertension should be carefully managed. Hypertension with a systolic reading is extremely harmful. As a result, there is increased interest in creating antihypertensive drugs with natural ingredients. The study's key finding is that Borassus flabellifer sap comprises significant bioactive components, including 9,10-Anthracenedione. The angiotensin-converting enzyme (ACE), which converts angiotensin I into the active peptide vasoconstrictor hormone angiotensin II, may be inhibited by Borassus flabellifer, according to an in-silico investigation. The 9,10-Anthracenedione and ACE molecular docking investigation revealed extremely low binding energy (-8.6 kcal/mol). One must be aware of the ACE inhibitors that are already on the market to choose an efficient ACE inhibitor. Docking interactions of 9,10-Anthracenedione hence strongly imply its potential as an antihypertensive substance. It is a possible bioactive Borassus flabellifer sap ingredient for the creation of nutraceuticals and functional foods, as well as a candidate for the development of an efficient antihypertensive medicine. According to the study's findings, Borassus flabellifer sap is a potent nutraceutical compound that can be used to treat antihypertensive.